The Collaborative Role Of Village Government And Prosecutor's Office In Corruption Prevention: A Case Study Of Buninagara Village, West Bandung District - Pertiwi, Shyntia Jashmin; Anindya, Galuh Rajni; Khoirunnisa, Zahra; Zahratunnisa, Alya; Salsabila, Ratsya (Action Research Literate, 2025)
This paper aims to determine the collaboration between the village government and law enforcement, known as prosecutor, in preventing corruption. Indonesia is a state that implements the law to uphold justice and truth. Based on Article 1 section (3) of Law Number 6 of 2014 concerning Village Governments, the Village Head, or referred to by another name, is assisted by the Village apparatus as an element of the Village Government organizer. Therefore, it is important in a village government to regulate and manage the interests of the local community, which are carried out by the Village Government organizers. In line with that, the village government collaborates with the prosecutor's office through various strategic steps, such as budget transparency and accountability, as a form of increasing more intensive supervision of village budget management. The prosecutor's office, as a law enforcement agency, is involved in providing legal guidance and assistance in efforts to prevent corruption, as well as taking applicable legal actions if indications of potential corruption cases are found. With this collaboration, it is hoped that a clean and transparent collaboration can be created at all levels of society, especially in government, as a joint effort to avoid corrupt practices.